2014
DOI: 10.1002/oby.20529
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors associated with weight loss outcomes after Roux‐en‐Y gastric bypass surgery

Abstract: OBJECTIVE Gastric bypass surgery is an effective therapy for extreme obesity. However, substantial variability in weight loss outcomes exists that remains largely unexplained. Our objective was to determine whether any commonly collected pre-operative clinical variables were associated with weight loss following Roux-en-Y gastric bypass surgery. DESIGN The analysis was based on a prospectively recruited observational cohort of 2365 patients who underwent Roux-en-Y gastric bypass surgery from 2004-2009. Weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
88
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 35 publications
13
88
2
5
Order By: Relevance
“…A summary of demographic and clinical characteristics of the final cohort (n=1868) is shown in Table 1. As is typical for patients enrolled in bariatric surgery programs [27], the population was primarily female (>81%). In addition, the percentage of males with grade 2 and 3 hepatic lipid content was significantly higher than in those without liver fat.…”
Section: Resultsmentioning
confidence: 99%
“…A summary of demographic and clinical characteristics of the final cohort (n=1868) is shown in Table 1. As is typical for patients enrolled in bariatric surgery programs [27], the population was primarily female (>81%). In addition, the percentage of males with grade 2 and 3 hepatic lipid content was significantly higher than in those without liver fat.…”
Section: Resultsmentioning
confidence: 99%
“…Overall impact of surgery on long term mortality reduction has already been observed on obese patients with 40% reduction on all causes mortality, 56% on coronary heart disease, 92% on diabetes complications and 60% on any type of cancer (1) . Nevertheless, some individuals may regain variable amounts of weight after a period of rapid weight loss, while others fail to lose significant weight despite the major structural and physiological changes brought by the surgery (22) . Hence, postsurgical weight loss failure constitutes a major concern since it is poorly understood and brings unsatisfactory outcomes and possible need of further interventions (12) .…”
Section: Introductionmentioning
confidence: 99%
“…The only factor we could find of significance to predict the time to SS was older patients had a shorter SS period compared to younger patients. Older age has previously been found to be a risk factor for higher nadir weight following gastric bypass [12,13]. Sugarman et al reported a significantly better %EWL and %BMI loss for patients <60 years old compared to patients >60 years of age after RYGB [14].…”
Section: Discussionmentioning
confidence: 97%